THE RELATIONSHIP OF STUDENTS' LEARNING MOTIVATION TO THEIR ACHIEVEMENT IN THE SUBJECT OF CREED OF ACHIEVEMENT - hilmi, fuad (CV. Media Publikasi Profesional, 2023)
Abstract: The main objective of this research is to identify and understand the relationship between learning motivation and student academic achievement. In order to achieve this goal, this research uses a quantitative analysis methodology based on inferential statistical models. This approach includes the use of regression and Pearson product moment correlation analysis to analyze the data obtained. This research is based on theoretical studies which state that there is a significant relationship between students' learning motivation and their academic achievement. By using regression techniques, researchers can identify the extent to which learning motivation variables influence student achievement. Meanwhile, Pearson product moment correlation analysis allows researchers to determine the strength and direction of the relationship between the two variables. Thus, this research not only aims to prove the existence of a relationship between learning motivation and student achievement, but also to understand the extent to which learning motivation can be a determining factor in improving student academic achievement. It is hoped that the results of this research can provide deeper insight for educators, policy makers and other related parties in an effort to improve the quality of education through increasing student learning motivation.